Fetal origins: A life cycle model of health and aging from conception to death - Carl-Johan Dalgaard; Casper Worm Hansen; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
The fetal origins hypothesis has received considerable empirical support, both within epidemiology and economics. The present study compares the ability of two rival theoretical frameworks in accounting for the kind of path dependence implied by the fetal origins hypothesis. We argue that while the conventional health capital model is irreconcilable with fetal origins of late-in-life health outcomes, the more recent health deficit model can generate shock amplification consistent with the hypothesis. In order to discuss human health over the life cycle from conception to death, we develop a theory of ontogenetic growth in utero and during childhood, unify it with the theory of adult aging, and discuss the transmission of early-life shocks to late-life health deficit accumulation.
Keywords: I10; J13; D91; 330; Fetal Origins; Health Capital; Health Deficits; Ontogenetic Growth; In Utero Development